Evaluation of elevated plasma fatty acids as relevant factors for adult-onset asthma: The Nagahama Study - Noriyuki Tashima; Hisako Matsumoto; Kenta Nishi; Satoru Terada; Mariko Kogo; Natsuko Nomura; Chie Morimoto; Hironobu Sunadome; Tadao Nagasaki; Tsuyoshi Oguma; Yoshinari Nakatsuka; Kimihiko Murase; et al. (Allergology International, 2024)
Background: Obesity and increased body mass index (BMI) are the known risk factors for adult-onset asthma. Serum free fatty acid (FFA) and other blood lipid levels are generally elevated in patients with obesity and may be involved in the onset of asthma. However, it remains largely unknown. This study aimed to elucidate the relationship between plasma fatty acids and new-onset asthma. Methods: This community-based Nagahama Study in Japan enrolled 9804 residents. We conducted self-reporting questionnaires, lung function tests, and blood tests at baseline and 5 years later as follow-up. At the follow-up, plasma fatty acids were measured using gas chromatography-mass spectrometry. Body composition analysis was also measured at the follow-up. The associations between fatty acids and new-onset asthma were evaluated using a multifaceted approach, including targeted partial least squares discriminant analysis (PLS-DA). Results: In PLS-DA for new-onset asthma, palmitoleic acid was identified as the fatty acid most associated with asthma onset. In the multivariable analysis, higher levels of FFA, palmitoleic acid, or oleic acid were significantly associated with new-onset asthma, independent of other confounding factors. The high body fat percentage itself was not the relevant factor, but showed a positive interaction with plasma palmitoleic acid for new-onset asthma. When stratified by gender, the impacts of higher levels of FFA or palmitoleic acid on new-onset asthma remained significant in females, but not in males. Conclusions: Elevated levels of plasma fatty acids, particularly palmitoleic acid, may be a relevant factor for new-onset asthma.